Overview control strategies of series, shunt, series/shunt FACTS devices for three stability functions of power system - Taghizadeh S.F.; Younis M.A.A.; Nikouei B.; Tan Nadia M.L.; Mekhilef S. (Praise Worthy Prize, 2023)
This paper represents an overview of three types of FACTS devices configurations, categorized by series, shunt and series-shunt consisting of TCSC, SVC and UPFC Such devices are the most famous Flexible AC Transmission System devices in the world. In the first section features of the devices are introduced briefly, and in the next section control schemes of each are classified and reviewed for three control functions of power system such as steady state stability, transient stability and power oscillation stability. The relevant issues are also considered and discussed. 2012 Praise Worthy Prize S.r.l. - All rights reserved.